Design and Performance of Policy Instruments to Promote the Development of Renewable Energy : Emerging Experience in Selected Developing Countries - Elizondo Azuela, Gabriela (Washington, DC: World Bank, 2012)
This report summarizes the results of a recent review of the emerging experience with the design and implementation of policy instruments to promote the development of renewable energy (RE) in a sample of six representative developing countries and transition economies ('developing countries') (World Bank 2010). The review focused mainly on price- and quantity-setting policies, but it also covered fiscal and financial incentives, as well as relevant market facilitation measures. The lessons learned were taken from the rapidly growing literature and reports that analyze and discuss RE policy instruments in the context of different types of power market structures. The analysis considered all types of grid-connected RE options except large hydropower: wind (on-shore and off-shore), solar (photovoltaic and concentrated solar power), small hydropower (SHP) (with capacities below 30 megawatts), biomass, bioelectricity (cogeneration), landfill gas, and geothermal. The six countries selected for the review included Brazil, India, Indonesia, Nicaragua, Sri Lanka, and Turkey.